The role of effective strategic leadership in transforming New Zealand’s work health and safety system - Koia, Henry (New Zealand Journal of Health and Safety Practice, 2024)
Hard working New Zealanders continue to die in New Zealand workplaces more than a decade after the Independent Taskforce on Workplace Health and Safety told us that all injuries and deaths in New Zealand workplaces are preventable. The single critical factor behind New Zealand’s poor workplace health and safety record is the gap in the provision of effective strategic leadership. Closing that fundamental gap will require the Minister who is for the time being responsible for the administration of the Health and Safety at Work Act 2015 to take accountability for the performance of the work health and safety system in meeting set harm prevention targets, and be answerable to the Prime Minister. To have any chance of upholding that accountability the Minister must lead effectively and strategically. To achieve that, the Minister’s strategic advisers must acquire many new insights generated from new thinking, theories, and models for aiding harm prevention such as the Chain of Interventions Model and the Risk Management Compliance Continuum Model.